Assessment of Binge-Like Eating of Unsweetened vs. Sweetened Chow Pellets in BALB/c Substrains - Sena, Katherine D.; Beierle, Jacob A.; Richardson, Kayla T.; Kantak, Kathleen M.; Bryant, Camron D. (Frontiers in Behavioral Neuroscience, 2022)
Binge eating disorder is defined as chronic episodes of consuming large amounts of food in less than 2 hours. Binge eating disorder poses a serious public health problem, as it increases the risk of obesity, type II diabetes, and heart disease. Binge eating is a highly heritable trait; however, its genetic basis remains largely unexplored. We employed a mouse model for binge eating that focused on identifying heritable differences between inbred substrains in acute and escalated intake of sucrose-sweetened palatable food versus unsweetened chow pellets in a limited, intermittent access paradigm. In the present study, we examined two genetically similar substrains of BALB/c mice for escalation in food consumption, incubation of craving after a no-food training period, and compulsive-like food consumption in an aversive context. BALB/cJ and BALB/cByJ mice showed comparable levels of acute and escalated consumption of palatable food across training trials. Surprisingly, BALB/cByJ mice also showed binge-like eating of the unsweetened chow pellets similar to the escalation in palatable food intake of both substrains. Finally, we replicated the well-documented decrease in anxiety-like behavior in BALB/cByJ mice in the light-dark conflict test that likely contributed to greater palatable food intake than BALB/cJ in the light arena. To summarize, BALB/cByJ mice show binge-like eating in the presence and absence of sucrose. Possible explanations for the lack of selectivity in binge-like eating across diets (e.g., novelty preference, taste) are discussed.